CHARACTERISTICS OF THE ISLAMIC EDUCATION MODEL OF NUSANTARA - Duwi Miyanto (Pascasarjana Universitas Wahid hasyim Semarang, 2025)
In this discussion only focus on the Character of The Model of Islamic Education Nusantara, in it discusses the model of education. This refers to science by ordering reading as the basis of science. The command to